Unicistes versus pluralistes : l’homéopathie brésilienne à l’ère de la globalisation - Armelle Giglio-Jacquemot (Anthropologie & Santé)
For firms, globalization represents a propitious framework for the circulation of merchandise and market expansion. In Brazil, the recent establishment of a subsidiary of the French laboratory Boiron has shaken the local field of homeopathy. Based on ethnographic fieldwork in São Paulo, this article particularly examines the reactions, strategies and changes caused by this implantation in Brazilian homeopathy and beyond. The study also looks into the way this pharmaceutical industry - which bears a certain conception of homeopathy and of homeopathic drugs - has had to adapt in order to distribute its products locally.